Implementation of the Hadith “al-Bayyinatu 'ala al-Mudda'i wa al-Yamin 'ala Man Ankara” in the DSN MUI Fatwa on Guaranteeing Capital Returns - Prima Ariyo Widodo; Abdur Rohman; Yuliyanto Eko Prayitno; Alam Firman Syah (Walidem Institute and Publishing (WIP), 2024)
This study aims to analyze the implementation of the hadith